Spotlight on Melphalan Flufenamide: An Up-and-Coming Therapy for the Treatment of Myeloma - Morabito F; Tripepi G; Martino EA; Vigna E; Mendicino F; Morabito L; Todoerti K; Al-Janazreh H; D'Arrigo G; Canale FA; Cutrona G; Neri A; et al. (Dove Medical Press, 2021)
Fortunato Morabito,1,2 Giovanni Tripepi,3 Enrica Antonia Martino,4 Ernesto Vigna,4 Francesco Mendicino,4 Lucio Morabito,5 Katia Todoerti,6 Hamdi Al-Janazreh,2 Graziella D'Arrigo,3 Filippo Antonio Canale,7 Giovanna Cutrona,8 Antonino Neri,6,8 Massimo Martino,9 Massimo Gentile4 1Biotechnology Research Unit, AO of Cosenza, Cosenza, Italy; 2Hematology and Bone Marrow Transplant Unit, Hemato-Oncology Department, Augusta Victoria Hospital, East Jerusalem, Israel; 3HCNR-IBIM, Clinical Epidemiology and Physiopathology of Renal Diseases and Hypertension of Reggio Calabria, Reggio, Calabria, Italy; 4Hematology Unit, AO of Cosenza, Cosenza, Italy; 5Humanitas Clinical and Research Center-IRCCS, Rozzano, Milan, Italy; 6Hematology, Fondazione Cà Granda IRCCS Policlinico, Milan, Italy; 7Stem Cell Transplant Program, Clinical Section, Department of Hemato-Oncology and Radiotherapy, Grande Ospedale Metropolitano "Bianchi-Melacrino-Morelli", Reggio, Calabria, Italy; 8IRCCS Ospedale Policlinico San Martino, Genoa, Italy; 9Department of Oncology and Hemato-oncology, University of Milan, Milan, ItalyCorrespondence: Fortunato MorabitoBiotechnology Research Unit, AO of Cosenza, Contrada San Nicola, Cosenza, Italy, Cosenza, 87100, ItalyTel +39-0984-015863Fax +39-0984-681329Email f.morabito53@gmail.comMassimo GentileHematology Unit, AO of Cosenza, Italy, viale della Repubblica snc, Cosenza, 87100, ItalyTel +39-0984-681329Fax +39-0984-681329Email massim.gentile@tiscali.itAbstract: Despite recent therapeutic advances, multiple myeloma (MM) patients experience relapses as they become resistant to various classes and combinations of treatment. Melphalan (L-PAM) is an ageless drug. However, its use in the autologous stem cell transplantation (ASCT) setting and the innovative quadruplet regimen as well as daratumumab, bortezomib, and prednisone make this old drug current yet. Melflufen is a peptide-conjugated alkylator belonging to a novel class of compounds, representing an overcoming of L-PAM in terms of mechanism of action and effectiveness. The improved melflufen cytotoxicity is related to aminopeptidase activity, notably present in normal and neoplastic cells and remarkably heavily overexpressed in MM cells. Upon entering a cell, melflufen is cleaved by aminopeptidases, ultimately releasing the L-PAM payload and eliciting further the inflow and cleavage of the conjugated peptide. This virtuous loop persists until all extracellular melflufen has been utilized. The aminopeptidase-driven accumulation results in a 50-fold increase in L-PAM cell enrichment as compared with free alkylator. This condition produces selective cytotoxicity, increased on-target cell potency, and decreased off-target cell toxicity, ultimately overcoming resistance pathways triggered by previous treatments, including alkylators. Due to its distinct mechanism of action, melflufen plus dexamethasone as a doublet, and in combination with other novel drugs, has the potential to be beneficial for a broad range of patients with relapsed/refractory (RR) MM in third- or even in second-line therapy. The safety profile of melflufen has been consistent across studies, and no new safety concerns have been identified when melflufen was administered in doublet and triplet combinations. Based on growing clinical evidence, melflufen could be not only a good addition in the fight against RRMM but also a drug with a very favorable tolerability profile.Keywords: multiple myeloma, relapsed resistant, melphalan flufenamide, melflufen, therapy, melphalan